ANALISIS MOTIVASI IBU RUMAH TANGGA BERBISNIS ONLINE (STUDI KASUS DISTRIK ARSO BARAT KABUPATEN KEEROM PROVINSI PAPUA) - Pratiwi, Ira Eka; Affandy, Fachrudin Fiqri; Fatma, Fatma (Raheema, 2023)
This study aims to analyze the motivations of housewives doing online business in the Arso Barat District, Keerom Regency, Papua Province. The method used in this research is quantitative statistics using primary data. The instrument used in this study was a questionnaire that had been tested for validity and reliability. Primary data were obtained from 50 respondents who are housewives who do online business in Arso Barat District, Keerom Regency. Analysis of the data used is to use multiple linear regression test. The results showed that self-actualization variabels significantly influence the motivation of housewives doing online business in the Arso Barat District, Keerom Regency. Meanwhile, the physiology needs variabel does not significantly influence the motivation of housewives doing online business in the Arso Barat District, Keerom Regency. The independence variabel also did not significantly influence the motivation of housewives to do online business in Arso Barat District, Keerom Regency.